(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, GdCUagGfj, eMeO MSf Hf HGbQ Hf YHO GdQMje, J (B1266(3g`s
(3ChdgG (B:s
(3GdQcf GdKGdK ef CQcGf GdUdGI aj HbjI GdUdhGJ hajg aUhd(B...s
(3BNQgG (B:s
...(3hY GJMGO GdUfa QGYi JKfjI GdVejQ hLeYg hJPcjQg hJCfjKg(B...s
(3CJe GdeDda JHjjVg aj (B24 (3QHjY GdKGfj (B1236(3g` , hgPg GdfSNI ebGHdI Ydi eShOI GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B92s
(3EjVGM Gdecfhf(B:(3L(B1(3,U(B378s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis